Measurement of Brand Awareness and Brand Loyalty of Goldstar Shoes - Amatya, Kailash Patendra (Management Dynamics, 2020)
The purpose of this study is to measure the degree of brand awareness and brand loyalty of Goldstar shoes among Nepalese consumers. The study has adopted descriptive research design. Data in the study are collected from primary data. A total of 70 respondents participated in this study. Data were analyzed using various tools such as tables and figures to draw the conclusion. The findings show that majority of consumers are aware about Goldstar shoes and associate them with durability, comfort and price attributes. However, this familiarity is not able to influence the purchase decision of consumers. The manufacturers should manufacturer footwear in various designs and styles using better materials that ensure comfort and durability to consumers along with maintaining reasonable pricing strategy to have a strong customer base loyalty.